Retrospective and prospective ovarian cancer comparison in few Iraqi provinces - Samira Abdul-Hussain Abdullah (Tikrit Journal of Pure Science)
Ovarian cancer is the second most common cause of death with cancer, and the third most common malignancy. Many factors considered to be risk factors, among that, age group, family history and marital status. A total of 183 samples were collected from three northern Iraqi provinces and one from the south. Patient women samples with ovarian cancer were collected from Kirkuk, Erbil, Sulaimannyah and Dhi Qar. Patients samples were collected during the period from first of January 2013 to the end of December 2013. The data were collected through a questionnaire.